Echinoderes unispinosus (Kinorhyncha: Cyclorhagida), a new record from deep-sea sediments in the Gulf of Mexico - Álvarez-Castillo, Lucia; Cepeda, Diego; Pardos, Fernando; Rivas, Gerardo; Rocha-Olivares, Axayácatl (Zootaxa, 2020)
Kinorhyncha is a phylum of exclusively marine, meiofaunal invertebrates (Sørensen & Pardos 2008). Currently, the knowledge about the worldwide distribution of most of its species is considerably patchy, as several taxa have been reported from a single or few localities, usually within a limited geographic area (Sørensen & Pardos 2008; Yamasaki et al. 2018a). This even becomes more evident for deep-sea kinorhynchs, as noticed by Sørensen et al. (2018). Given the particular value of new records from the deep-sea to increase our understanding in the distribution of meiofaunal organisms plus the observed relationship of morphological variation through the bathymetric gradient, we aim to report the first record of Echinoderes unispinosus Yamasaki, Neuhaus & George, 2018 in the southern edge of the Gulf of Mexico (GoM), and contribute with new information about the morphological intraspecific variation of this species. In Mexico, studies of kinorhynch biodiversity are limited to the northern Gulf of California (50–1570m depth) (Álvarez-Castillo et al. 2015, 2018; Cepeda et al. 2019) and the Yucatán Peninsula (Sánchez & Martínez 2019). The GoM is a semi-closed basin located in a transition zone with both subtropical and tropical weather. Deep-sea muddy sediment samples of the present study were collected during the expedition XIXIMI-5 (10–24 June 2016) and processed according to Cisterna-Céliz et al. (2019). Kinorhynch specimens were mounted, measured and photographed according to Cepeda et al. (2019). Two adult males were identified as E. unispinosus, one from station B11 (2298 m depth) and another from station B15 (3708m depth). Kinorhynch specimens were deposited at the Aquatic Invertebrates Collection of the Facultad de Ciencias, Universidad Nacional Autónoma de México (UNAM), Mexico, under accession numbers: KGM.001 and KGM.002.